Agonist that activates the µ-opioid receptor in acidified microenvironments inhibits colitis pain without side effects. Issue 4 (30th March 2021) - Jiménez-Vargas, Nestor Nivardo; Yu, Yang; Jensen, Dane D; Bok, Diana Daeun; Wisdom, Matthew; Latorre, Rocco; Lopez, Cintya; Jaramillo-Polanco, Josue O; Degro, Claudius; Guzman-Rodriguez, Mabel; Tsang, Quentin; Snow, Zachary; et al.
Abstract : Objective: The effectiveness of µ-opioid receptor (MOPr) agonists for treatment of visceral pain is compromised by constipation, respiratory depression, sedation and addiction. We investigated whether a fentanyl analogue, (±)-N-(3-fluoro-1-phenethylpiperidine-4-yl)-N-phenyl propionamide (NFEPP), which preferentially activates MOPr in acidified diseased tissues, would inhibit pain in a preclinical model of inflammatory bowel disease (IBD) without side effects in healthy tissues. Design: Antinociceptive actions of NFEPP and fentanyl were compared in control mice and mice with dextran sodium sulfate colitis by measuring visceromotor responses to colorectal distension. Patch clamp and extracellular recordings were used to assess nociceptor activation. Defecation, respiration and locomotion were assessed. Colonic migrating motor complexes were assessed by spatiotemporal mapping of isolated tissue. NFEPP-induced MOPr signalling and trafficking were studied in human embryonic kidney 293 cells. Results: NFEPP inhibited visceromotor responses to colorectal distension in mice with colitis but not in control mice, consistent with acidification of the inflamed colon. Fentanyl inhibited responses in both groups. NFEPP inhibited the excitability of dorsal root ganglion neurons and suppressed mechanical sensitivity of colonic afferent fibres in acidified but not physiological conditions. Whereas fentanyl decreased defecation and caused respiratory depression and hyperactivity in mice with colitis, NFEPP was devoid of these effects. NFEPP did not affect colonic migrating motor complexes at physiological pH. NFEPP preferentially activated MOPr in acidified extracellular conditions to inhibit cAMP formation, recruit β-arrestins and evoke MOPr endocytosis. Conclusion: In a preclinical IBD model, NFEPP preferentially activates MOPr in acidified microenvironments of inflamed tissues to induce antinociception without causing respiratory depression, constipation and hyperactivity.